GnRH Administration in the Synchronization of Receptors Cows for Fixed-Time Embryo Transfer - Messias, Dyórgenes Mathaus Perosso; Cavalieri, Fábio Luiz Bim; Andreazzi, Márcia Aparecida; Santos, José Maurício Gonçalves dos; Emanuelli, Isabele Picada; Colombo, Antonio Hugo Bezerra; Moreski, Danieli Aparecida Bóbbo (Journal of Agricultural Studies, 2022)
The bovine production chain in Brazil is highlighted worldwide; however, researchers are seeking to improve production even further by evaluating the use of reproductive biotechnologies, such as the transfer of embryos at a fixed time. The aim of this study was to analyze the expression of estrus associated or not with the use of gonadotropin releasing hormone (GnRH), on the diameter of the dominant follicle, diameter of the corpus luteum, utilization rate and conception rate of receptors cows. The experiment was carried out in southern Brazil and 400 receptors cows were used, distributed in a 2x2 factorial scheme, considering estrus expression and GnRH administration. All receptors were synchronized and, on Day 10, their ovaries were evaluated and, based on estrus expression, they were distributed into 2 subgroups: with and without GnRH application. On Day 18, they had their ovaries evaluated and they were inovulated, and on Day 41, the pregnancy diagnosis was made. The expression of estrus increased the diameter of the dominant follicle and corpus luteum and the utilization rate of the recipient cows; however, it did not improve the conception rate. The administration of GnRH, with or without the expression of estrus, did not affect any of the studied variables.